The Role Of Fibrosis And Immune Inflammation In Depression In Patients With Ischemic Stroke: Life Sciences-Health - A. Osipova, Olga; V. Gosteva, Elena; I. Kluishnikov, Nikolai; V. Kaliuzhnaya, Elena; A. Shabalin, Alexey (International Journal of Life Science and Pharma Research, 2022)
Nowadays, Stroke is regarded as the second major cause of death and the third major cause of morbidity globally. The ischemic stroke (IS) is among the most fatal kind of strokes. Thus, due to the importance of this subject, this article aims to analyze the role of fibrosis markers (matrix metalloproteinase-9, tissue inhibitor of matrix metalloproteinases-1), cytokines (tumor necrosis factor-α, interferon-γ, monocytic chemoattractant protein-1) in the development of post-stroke depression in elderly patients with arterial hypertension (AH). To that end, the study included 114 elderly patients with the first acute ischemic stroke; the average age of the patients was 68 ± 7 years. The control group consisted of 20 older people without hypertension and a history of stroke. The level of matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of matrix metalloproteinases-1 (TIMP-1) was determined by ELISA (ELISA Kit, USA); the level of tumor necrosis factor-α (TNF-α), interferon-γ (INF-γ), monocytic chemoattractant protein-1 (MCP-1) - JSC "Vector-Best", Russia. After 3 months of observation of patients, post-stroke depression (PD) developed in 50 people. (43.8%). Patients who developed PD were significantly older (9.4%, p <0.05), a higher body mass index by 12.2% (p <0.05), a glycemic level by 16.1% (p <0, 05), triglycerides by 14.0% (p <0.05), LDL by 12.8% (p <0.05) than in patients without depression. Patients with ischemic stroke and PD had higher levels of cytokines - TNF-α by 23.8% (p <0.01), INF-γ by 17.5% (p <0.01), MCP-1 by 17, 6% (p <0.01), the level of MMP-9 was higher by 15.3% (p <0.05), TIMP-1 - by 11.4% (p <0.05). Thus, in elderly patients with hypertension with ischemic stroke, the level of fibrosis and inflammation markers may have a prognostic value in developing post-stroke depression. Hence, this article could greatly contribute to the alleviation of depression in patients with ischemic stroke.